The Success of the Vaccine Policy in Treating Covid-19 in Indonesia - DEVIA ANDIANI; RETNOWATI WD TUTI; EVI SATISPI; AZHARI AZIZ SAMUDRA; NIDA HANDAYANI; NANY WIDIASTUTI (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2023)
The Covid-19 pandemic has created new problems for various countries hit by this pandemic, especially regarding how the country’s efforts are to pre- vent and stop the spread of the COVID-19 pandemic so that it does not become wider and cause more victims. The covid-19 vaccine is one of the policies taken by many countries in response to the covid-19 pandemic. The purpose of this study was to find out how successful the vaccination policy was in handling the Covid-19 pandemic in Indonesia. The research method used in this study is Literature Review, the data used is to collect several research papers related to the covid-19 vaccination policy. The results of the research related to the success of the vaccination policy as a response to the Covid-19 pandemic in Indonesia can be said to be successful, because the level of attainment of vaccine doses continues to increase, then positive cases of COVID-19 continue to sag, although there are still pros and cons in the community, and there are also cases of the public’s distrust of the covid-19 vaccine, the biggest obstacle due to the lack of clarity of information regarding the corona vaccination, these obstacles can be input for the government to further accelerate the vaccination program. The government itself has targeted vaccination to reach 2 million doses a day, and also the occurrence of public distrust with the covid-19 vaccine.